1988
DOI: 10.1038/bjc.1988.213
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of doxorubicin and cis-platin in squamous carcinoma cells in culture

Abstract: Summary Doxorubicin (DXR) has a positive inoculum effect and penetrates poorly into the core of multicellular tumour spheroids (MTS). Cis-platin (DDP) displays neither of these characteristics. We evaluated whether combining these 2 agents would influence the cell kill effect at a tumour mass level. MTS were produced from a PC-10 squamous lung carcinoma cell line. MTS were exposed to either drug first for h with different intervals between exposure. Cells were then trypsinized to a single cell suspension and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…29 A different incubation time with cisplatin may be required to observe an enhancement since this agent's sensitizing property was shown to be time-dependent both in vitro and in vivo. 29,31 We observed no LDh release (white bars) was measured (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…29 A different incubation time with cisplatin may be required to observe an enhancement since this agent's sensitizing property was shown to be time-dependent both in vitro and in vivo. 29,31 We observed no LDh release (white bars) was measured (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
“…6,15,25,26 We evaluated combinations of clinically relevant drugs belonging to different groups: mitoxantrone (anthracenedione), cisplatin (alkylating-like), dexamethasone (glucocorticosteroid), methotrexate (antifolate), sclareol (labdane diterpene), paclitaxel (taxane) and doxorubicin (anthracycline). In vitro use of these drugs in combination protocols was reported for sclareol and methotrexate, 27,28 in vivo for paclitaxel, cisplatin and dexamethasone; 8,[29][30][31] and with patients for doxorubicin, paclitaxel, mitoxantrone and methotrexate. [16][17][18][32][33][34] Their sequential combination with doxorubicin in a spheroid model was studied in this report.…”
Section: Introductionmentioning
confidence: 99%
“…Because 3D multicellular tumor spheroids provide a microenvironment that mimics tumors in vivo, (10) spheroid culture has been used to evaluate tumor cell invasiveness and ⁄ or its responsiveness to anticancer drugs. (11)(12)(13)(14)(15) At IC 10 determined in monolayer culture, both cisplatin or docetaxel did not affect filopodia formation. However, at IC 50 also determined in monolayer culture, docetaxel, but not cisplatin, significantly decreased filopodia formation in HEp-2 cells in spheroid culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The failure of postoperative intraperitoneal drug administration may be correlated with heterogeneous drug distribution caused by early postoperative adhesions entrapping tumor cells and protecting them from the chemotherapeutic agents 23. In addition, some antineoplastic drugs (e.g., doxorubicin and cisplatin) act synergistically with each other24, 25 and with heat,26, 27 which led some authors to propose hyperthermic intraperitoneal intraoperative chemotherapy (HIIC) for the treatment of locally advanced intraabdominal malignancies 17, 28. The results of cytoreductive surgery combined with HIIC for the treatment of gastrointestinal carcinomas have been encouraging 18, 29–38.…”
mentioning
confidence: 99%
“…As a single drug regimen, it has been administered intraperitoneally in patients with advanced ovarian carcinoma, but patients develop high local toxicity 40. Some studies demonstrated in preclinical models that doxorubicin activity is enhanced by the addition of cisplatin24, 25 and/or hyperthermia 26, 27, 41. This potential synergy might be exploited to reduce the doxorubicin dosage (and thus minimize doxorubicin‐related local toxicity) while still maintaining the therapeutic activity of the cytotoxic regimen.…”
mentioning
confidence: 99%